Strategi Komunikasi Dakwah Ustadzah Riskiyah dalam Majelis Ta’lim Perempuan di Desa Kertagena Tengah - Fadilatul Kamilah; Fikrah Ainiyatun; Fahrur Rozi; Imam Sadili (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2026)
Women play an important role in strengthening religious life and social cohesion within their communities. The Majelis Taklim Perempuan (Women's Islamic Study Group) serves as a forum for learning Islamic teachings, sharing religious experiences, and fostering solidarity among members. In Kertagena Tengah Village, this study group is led by Ustadzah Riskiyah, who applies various da'wah communication strategies to improve participants' religious understanding and encourage the application of Islamic values in daily life. This study aims to analyze the communication strategies employed by Ustadzah Riskiyah and evaluate their effectiveness in supporting women's religious development. This research employed a qualitative field research approach. Data were collected through participant observation of study group activities, in-depth interviews with Ustadzah Riskiyah and selected congregation members, and documentation of religious activities. The data were analyzed descriptively using qualitative techniques to identify communication patterns, message delivery strategies, and participant responses throughout the learning process. The findings indicate that Ustadzah Riskiyah successfully combines interpersonal communication, simple and understandable language, interactive lectures, question-and-answer sessions, discussions, and exemplary behavior in delivering da'wah messages. These strategies encourage active participation, improve religious understanding, and motivate participants to practice Islamic teachings consistently in their daily lives. They also strengthen emotional relationships between the preacher and the congregation, creating trust and increasing the effectiveness of communication. The study concludes that adaptive and participatory communication strategies effectively empower women, strengthen religious commitment, and enhance the role of the Majelis Taklim as an important institution for community-based Islamic education and sustainable religious development in Kertagena Tengah Village.